ANALYTICAL STUDY OF THE TECHNOLOGICAL PARAMETERS OF THE TUBULAR-COMB FEEDER FOR FLUID MATERIALS - ВОЛЯНИК, О. Ю.; КОВАЛЬОВ, Ю. А.; РУБАНКА, М. М. (Technologies and Engineering, 2024)
The purpose of the study is an analytical investigation of the influence of rotation speed on the productivity of the tubular-comb feeder. The object of the research is the process of transporting bulk materials in the tubular-comb feeder. Methodology. Analytical review of literature sources. Analytical and experimental studies of the dependency of productivity on angular velocity, structural and technological parameters of the feeder, taking into account the physical properties of the bulk material. Research results. The critical angular velocity of the tube, at which the material does not detach from the walls, has been determined. A mathematical model of material transportation considering feeder parameters has been developed. Effective values of angular velocity for achieving maximum productivity have been identified. Dependencies of productivity on the tube's angular velocity have been obtained. An analysis of productivity considering structural parameters and properties of the bulk material has been conducted. The results of analytical calculations have been experimentally confirmed. Scientific novelty. A mathematical model has been developed that takes into account the physical properties of the material, feeder geometry, and operating parameters. It allowed describing the material transportation process and establishing the relationship between operating parameters and feeder productivity, determining the values of critical angular velocity ensuring the effective operation of the tubular-comb feeder. Practical significance. The obtained results can be used to improve the efficiency and functionality of tubular-comb feeders in industrial processes involving bulk materials. The research results are presented in the form of graphs showing the dependency of feeder productivity on the rotation speed of the feeder tube. This allows analyzing and comparing the efficiency of different feeder settings.